A case of torsion of the wandering spleen presenting as hypersplenism and gastric fundal varices - Kader Irak,; İrfan ESEN,; Murat Keskin,; Ahmet Tarık Eminler,; Talat AYYILDIZ,; Ekrem Kaya,; Murat KIYICI,; Selim GÜREL,; Selim Giray Nak,; Macit GÜLTEN,; Enver Dolar, (Turkish Journal of Gastroenterology, 2019)
-